DETERMINATION OF THE SECOND TWILIGHT BRIGHTNESS BY THE METHOD OF THE TWILIGHT PROBING OF THE EARTH’S ATMOSPHERE - Zaginailo, Yu. I. (Одеські астрономічні публікації, 2017)
A new method of ’gradients’ for determination of the secondary twilight brightness is proposed, which allows to determine the brightness of secondary twilight directly from the observations.